You, your child, and school navigate your way to the best education - Ken Robinson and Lou Aronica (New York, New York Viking, 2018)
"An essential book for parents to help their children get the education they need to live happy, productive lives from The New York Times bestselling author of The Element and Creative Schools. Parents everywhere are deeply concerned about the education of their children, especially now, when education has become a minefield of politics and controversy. One of the world's most influential educators, Robinson has had countless conversations with parents about the dilemmas they face. As a parent, what should you look for in your children's education? How can you tell if their school is right for them and what can you do if it isn't? In this important new book, he offers clear principles and practical advice on how to support your child through the K-12 education system, or outside it if you choose to homeschool or un-school. Dispelling many myths and tackling critical schooling options and controversies, You, Your Child, and Schoolis a key book for parents to learn about the kind of education their children really need and what they can do to make sure they get it"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Education--Parent participation